High-voltage-resistant lithium battery electrolyte and preparation method thereof

CN119297410AActive Publication Date: 2025-01-10HUNAN DAJING NEW MATERIAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411823684.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-10
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Traditional lithium battery electrolytes have poor stability, low ion transport efficiency, great influence on impurities, and poor performance instability and compatibility caused by uneven solvent mixing.

Method used

The nano-grade particle additives and lithium salts are prepared by high-speed magnetic stirring, ultrasonic dispersion and solvent-thermal method. Combined with high vacuum degassing and ultrafiltration membrane filtration, a stable solvation structure is formed, and the preparation environment is accurately controlled by an ultra-clean laboratory, and special Functional solvents and new additives are used to perform electrolyte aging treatment and comprehensive performance testing.

Benefits of technology

It significantly improves the stability, ion transmission efficiency and compatibility of the electrolyte, reduces the risk of impurity pollution, extends the battery cycle life, and improves the safety and performance of the battery in high-voltage environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-voltage-resistant lithium battery electrolyte and a preparation method thereof, and relates to the technical field of lithium battery electrolytes.The preparation method of the lithium battery electrolyte comprises the steps that S1, a basic solvent and a special functional solvent are mixed; s2, dispersing an additive and a lithium salt in a mixed solution of a basic solvent and a special functional solvent to obtain an electrolyte crude product; s3, purifying an electrolyte crude product; s4, performing electrolyte aging treatment; and S5, carrying out performance detection on the electrolyte subjected to aging treatment. The basic solvent and the special functional solvent are fully and uniformly mixed, and through the synergistic effect of air purification, temperature and humidity regulation and control, powerful impurity removal and a parameter monitoring system of an ultra-clean laboratory, the problems that an existing lithium battery electrolyte is poor in stability, low in ion transmission efficiency and large in impurity influence in a high-voltage environment, and the service life of the lithium battery electrolyte is long can be solved. And the problems of unstable electrolyte performance and poor compatibility with an electrode material caused by non-uniform solvent mixing are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery electrolytes, in particular to a high-voltage resistant lithium battery electrolyte and a preparation method thereof. Background Art

[0002] Traditional lithium battery electrolytes cannot effectively meet the stability requirements under high-voltage environments, resulting in a decrease in battery performance under high-voltage conditions. At the same time, the transmission efficiency of ions in the electrolyte is low, affecting the battery's charge and discharge rate and energy density. The lithium battery electrolyte of the present application can solve the problems of poor stability of existing lithium battery electrolytes under high-voltage environments, low ion transmission efficiency and large impurity influence, as well as unstable electrolyte performance and poor compatibility with electrode materials caused by uneven solvent mixing.

[0003] The defects of existing lithium battery electrolytes are: Patent document JP4754323B2 discloses a lithium battery electrolyte and a lithium battery. The document mainly considers how to improve the safety of the battery, but does not consider how to solve the problems of poor stability of existing lithium battery electrolytes under high-voltage environments, low ion transmission efficiency, and large impurity impact, as well as unstable electrolyte performance and poor compatibility with electrode materials caused by uneven solvent mixing; Patent document KR102020194B1 discloses a lithium battery electrolyte metering device. The document mainly considers how to increase the capacity, life and safety of the battery system, but does not consider how to solve the problem of impurities mixed in and preparation parameter fluctuations caused by environmental factors, thereby affecting the quality of the electrolyte; Patent document CN111261924B discloses a lithium battery electrolyte and a lithium battery. The document mainly considers how to increase the initial capacity of the battery, inhibit the increase of internal resistance, improve the normal temperature cycle performance and high temperature expansion, but does not consider how to solve the problem of rapid performance degradation and insufficient safety of ordinary electrolytes during long-term use of the battery; Patent document CN113972395B discloses a lithium battery electrolyte and a lithium battery. The document mainly considers how to overcome the problems of poor cycle performance and safety of existing lithium batteries, but does not consider how to solve the problem that uneven electrolyte quality affects the overall performance and quality stability of the battery. Summary of the invention

[0004] The object of the present invention is to provide a high-voltage resistant lithium battery electrolyte and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-voltage resistant lithium battery electrolyte, the method for preparing a lithium battery electrolyte comprising: S1. Add the base solvent into the mixing container and stir with a high-speed magnetic stirrer at a stirring speed of 800 rpm for 30 minutes, then add the special functional solvent and continue stirring for 48 minutes. The mixing mass ratio of the base solvent to the special functional solvent is 7:3-9:2. S2. The additive is made into nano-sized particles by ultrasonic dispersion method, the lithium salt is prepared into nano-sized crystals by solvothermal method, and the nano-sized particle additive and the nano-sized crystalline lithium salt are dispersed in a mixed solution of a basic solvent and a special functional solvent to obtain a crude electrolyte; S3, degassing the crude electrolyte under a high vacuum environment, with the vacuum degree reaching below 0.005 KPa, and removing impurities and solid particles through an ultrafiltration membrane filter, the pore size of the ultrafiltration membrane filter is 28-48 nm, to obtain a purified electrolyte; S4, placing the electrolyte in a constant temperature box, connecting the nitrogen supply pipeline and opening the constant temperature box to perform electrolyte aging treatment; S5. Performing performance testing on the electrolyte after aging treatment; The base solvent includes propylene carbonate, diethyl carbonate and ethyl methyl carbonate, and the molar ratio of propylene carbonate, diethyl carbonate and ethyl methyl carbonate is 3:1:2; The special functional solvent includes fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate, the addition amount of the special functional solvent is 10%-15% of the total mass of the base solvent, and the molar ratio of fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate is 1:1:2-2:1:3; The clean room is equipped with air purification system, temperature and humidity control system, powerful impurity removal system and parameter monitoring system.

[0006] Preferably, the air purification system achieves the function of removing tiny particles and harmful chemicals in the air and preventing microbial contamination through a composite filtration module, a particle removal module and a chemical adsorption module; The composite filtration module includes a glass fiber filter paper layer, a polypropylene meltblown cloth layer and an activated carbon fiber layer which are stacked in sequence. The particle removal module uses the electrostatic adsorption principle to remove particles with a particle size greater than 0.1 microns, and the chemical adsorption module uses modified silica gel to adsorb harmful chemicals.

[0007] Preferably, the temperature and humidity control system realizes the functions of controlling the temperature within the range of ±0.5°C and adjusting the humidity within the range of ±3%RH through a heating module, a cooling module, a humidification module and a dehumidification module; The heating module adopts ceramic heating plate, the cooling module adopts semiconductor cooling plate, the humidification module adopts ultrasonic humidifier, and the dehumidification module adopts molecular sieve desiccant.

[0008] Preferably, the powerful impurity removal system realizes the functions of filtering solid impurities, deeply removing water from the solvent and thoroughly removing dissolved gases through a filtering module, a vacuum dehydration module and an inert gas purge module; The filtration module uses a polyethersulfone ultrafiltration membrane with a molecular weight cutoff of 6000-9000Da. The vacuum degree of the vacuum dehydration module is maintained at 0.01-0.05KPa. The inert gas purge module uses argon with an argon flow rate of 10-20L / min. The parameter monitoring system monitors temperature, pressure and flow parameters, controls the stirring speed, and records the monitoring data through temperature sensors, pressure sensors, flow sensors, stirring speed controllers and data recording modules; The temperature sensor adopts a platinum resistance temperature sensor, the pressure sensor adopts a piezoresistive pressure sensor, and the flow sensor adopts an electromagnetic flowmeter.

[0009] Preferably, the additives include a novel film-forming additive, an anti-knock additive and a self-repairing additive, and the molar ratio of the film-forming additive, the anti-knock additive and the self-repairing additive is 4:1.5:1; The film-forming additive is one or more of vinylene carbonate or fluoroethylene carbonate, the anti-knock additive is one or more of trimethyl phosphate or triphenylphosphine, and the self-repairing additive is polyvinylidene fluoride.

[0010] Preferably, the lithium salt is lithium tetrafluoroborate, lithium bistrifluoromethanesulfonyl imide and lithium trifluoromethanesulfonate, and the molar ratio of lithium tetrafluoroborate, lithium bistrifluoromethanesulfonyl imide and lithium trifluoromethanesulfonate is 2:1:2-4:1:3.

[0011] Preferably, the frequency of ultrasonic dispersion is 26-43 kHz, the power is 120-270 W, the solvent thermal reaction temperature is 160-190° C., and the reaction time is 7-11 hours.

[0012] Preferably, the temperature of the thermostat is set at 28° C., nitrogen is introduced after the temperature stabilizes, the nitrogen flow rate is 0.6 liters per minute, the aging time is 10 days, and samples are taken every 8 hours during the aging process for performance testing.

[0013] Preferably, the detection parameters include conductivity, oxidation potential, reduction potential, lithium ion transference number, viscosity, density, moisture content, impurity content, fluoride stability, high pressure stability, thermal stability, appearance change, odor change and microstructure change.

[0014] Preferably, a high-voltage-resistant lithium battery electrolyte is prepared according to a method for preparing a high-voltage-resistant lithium battery electrolyte.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adds a special functional solvent, which contains fluorinated and perfluorinated compounds. The fluorine atom has a large electronegativity and a small radius, which can enhance the intermolecular force of the solvent and improve the anti-oxidation and decomposition resistance of the electrolyte. When the high-voltage lithium battery is charged and discharged, the electrode potential is high, and the electrolyte is easily oxidized and decomposed to generate gas and precipitation, which damages the battery performance. The present invention fully and evenly mixes the base solvent and the special functional solvent to form a stable solvation structure, adjusts the dielectric constant and viscosity of the electrolyte, and the carbonate base solvent provides a basic dielectric environment, which is conducive to the ionization of lithium salts. The fluorinated special functional solvent fine-tunes the viscosity to avoid excessive viscosity. It hinders the movement of ions, or the viscosity is too low to cause the growth of lithium dendrites. The appropriate dielectric constant ensures that the lithium salt is fully dissociated into free-moving ions. The optimized viscosity allows the ions to migrate and diffuse quickly at the interface between the electrode and the electrolyte, thereby improving the battery's charge and discharge rate performance and Coulomb efficiency. At the same time, it can reduce the activity of solvent molecules, reduce oxidative decomposition, maintain the stability of the electrolyte chemical composition, adapt to high-voltage environments, and extend the battery cycle life. Therefore, it can solve the problems of poor stability of existing lithium battery electrolytes under high-voltage environments, low ion transfer efficiency, and large impurity influence, as well as unstable electrolyte performance and poor compatibility with electrode materials caused by uneven solvent mixing.

[0016] 2. The present invention realizes precise control of the preparation environment through the synergistic effect of the air purification, temperature and humidity control, strong impurity removal and parameter monitoring system of the ultra-clean laboratory. The composite filtration module in the air purification system intercepts large particles of impurities in the air from a macro level, the particle removal module uses electrostatic adsorption to accurately remove tiny particles, and the chemical adsorption module adsorbs harmful chemicals, effectively preventing impurities from contaminating the electrolyte. The temperature and humidity control system strictly controls the ambient temperature and humidity within a very small fluctuation range through advanced heating, cooling, humidification and dehumidification modules, avoiding problems such as solvent volatilization and lithium salt crystallization caused by changes in temperature and humidity. The multi-module combination of the strong impurity removal system deeply removes solid impurities, moisture and dissolved gases from the solvent, ensuring the high purity of the solvent. The parameter monitoring system provides real-time feedback on the parameters of each link to ensure the accuracy of the preparation process. Compared with the existing technology, the purity of the electrolyte and the controllability of the preparation process can be improved, the risk of impurity introduction can be greatly reduced, and the quality of each batch of electrolyte can be stabilized at a high level. Therefore, the problem of impurity mixing and preparation parameter fluctuations caused by environmental factors, thereby affecting the quality of the electrolyte, can be solved. It provides a reliable technical guarantee for the large-scale and high-quality production of lithium battery electrolytes, and improves production efficiency and product qualification rate.

[0017] 3. The present invention uses ultrasonic dispersion and solvothermal method to prepare nano-scale additives and lithium salts, and adds new film-forming additives, anti-explosion additives and self-repairing additives to optimize the electrochemical performance and safety of the electrolyte. Ultrasonic dispersion at a specific frequency and power can evenly refine the additives into nano-scale particles, making them more dispersible in the electrolyte and more efficient. Nano-scale lithium salt crystals prepared by solvothermal method have higher activity and stability. New film-forming additives such as vinylene carbonate or fluoroethylene carbonate can form a dense, stable and ion-conductive SEI film on the electrode surface, effectively reducing the side reactions between the electrode and the electrolyte and improving the cycle life. The anti-explosion additives trimethyl phosphate or triphenylphosphine can inhibit the occurrence of thermal runaway reactions when the battery is abnormally heated or overcharged, thereby enhancing safety. The self-repairing additive polyvinylidene fluoride can repair the microcracks caused by volume changes in the electrode material during the battery charging and discharging process, and maintain the integrity of the electrode structure. Compared with existing technologies, it can improve the cycle life, safety and explosion resistance of batteries, significantly reduce the capacity decay rate of batteries during long-term use, and enhance the safety of batteries under extreme conditions. Therefore, it can solve the problems of rapid performance degradation and insufficient safety of ordinary electrolytes during long-term use of batteries, laying a solid foundation for the widespread application of high-performance lithium batteries in electric vehicles and energy storage.

[0018] 4. The present invention achieves strict control of the quality of the electrolyte by performing high vacuum degassing, ultrafiltration membrane filtration, aging treatment and comprehensive performance testing on the crude electrolyte. High vacuum degassing can effectively remove dissolved gases in the electrolyte to avoid the formation of air cavities during the battery charging and discharging process that affect the battery performance. Ultrafiltration membrane filtration uses ultrafiltration membranes with specific pore sizes to accurately remove impurities and solid particles, further improving the purity of the electrolyte. Aging treatment at a specific temperature, nitrogen atmosphere and aging time in a constant temperature box promotes further stabilization and homogenization between the components of the electrolyte, and sampling and testing at specific intervals can promptly discover potential problems and adjust the process. Comprehensive performance testing covers many key parameters such as the conductivity and oxidation potential of the electrolyte, ensuring the quality reliability of the electrolyte. Compared with the existing technology, the consistency and reliability of the electrolyte can be improved, so that each batch of electrolyte produced has highly consistent performance, and can stably provide an excellent electrochemical environment for lithium batteries. Therefore, it can solve the problem of uneven electrolyte quality affecting the overall performance and quality stability of the battery, which will help lithium battery manufacturers to improve product quality stability, reduce after-sales costs, and enhance market competitiveness. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Embodiment 1, a method for preparing a high-voltage resistant lithium battery electrolyte, the method for preparing the lithium battery electrolyte comprising: S1, add 70g of the base solvent to a mixing container, stir at 800rpm for 30 minutes, then add 30g of the special functional solvent, and continue stirring for 48 minutes; The base solvent includes propylene carbonate, diethyl carbonate and ethyl methyl carbonate, and the molar ratio of propylene carbonate, diethyl carbonate and ethyl methyl carbonate is 3:1:2; The special functional solvent includes fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate, the addition amount of the special functional solvent is 10% of the total mass of the base solvent, and the molar ratio of fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate is 1:1:2; S2. The additive is made into nano-scale particles by ultrasonic dispersion method, the ultrasonic frequency is 26kHz, the power is 120W, the lithium salt is prepared into nano-scale crystals by solvent thermal method, the solvent thermal reaction temperature is 160°C, the reaction time is 7 hours, and the nano-scale particle additive and the nano-scale crystalline lithium salt are dispersed in a mixed solution of a base solvent and a special functional solvent to obtain a crude electrolyte; The additives include a new film-forming additive, an anti-knock additive and a self-repairing additive, the molar ratio of the film-forming additive, the anti-knock additive and the self-repairing additive is 4:1.5:1, and the film-forming additive, the anti-knock additive and the self-repairing additive are vinylene carbonate, trimethyl phosphate and polyvinylidene fluoride, respectively; The lithium salt is lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide) and lithium trifluoromethanesulfonate, and the molar ratio of lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide) and lithium trifluoromethanesulfonate is 2:1:2; S3, placing the crude electrolyte in a high vacuum environment for degassing, the vacuum degree reaches below 0.005 KPa, and using an ultrafiltration membrane filter with a pore size of 28 nm to remove impurities and solid particles to obtain a purified electrolyte; S4. Place the electrolyte in a 28°C constant temperature box. After the temperature stabilizes, introduce nitrogen at a rate of 0.6 liters per minute. The aging time is 10 days. During the aging process, samples are taken every 8 hours for performance testing.

[0021] Embodiment 2, a method for preparing a high-voltage resistant lithium battery electrolyte, the method for preparing the lithium battery electrolyte comprising: S1, add 80g of the base solvent into a mixing container, stir at 800rpm for 30 minutes, then add 20g of the special functional solvent, and continue stirring for 48 minutes; The base solvent includes propylene carbonate, diethyl carbonate and ethyl methyl carbonate, and the molar ratio of propylene carbonate, diethyl carbonate and ethyl methyl carbonate is 3:1:2; The special functional solvent includes fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate, the addition amount of the special functional solvent is 13% of the total mass of the base solvent, and the molar ratio of fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate is 1.5:1:2.5; S2. The additive is made into nano-sized particles by ultrasonic dispersion method, the ultrasonic frequency is 35kHz, the power is 200W, the lithium salt is prepared into nano-sized crystals by solvent thermal method, the solvent thermal reaction temperature is 175°C, the reaction time is 9 hours, and the nano-sized particle additive and the nano-sized crystalline lithium salt are dispersed in a mixed solution of a basic solvent and a special functional solvent to obtain a crude electrolyte; The additives include a novel film-forming additive, an anti-knock additive and a self-repairing additive, wherein the molar ratio of the film-forming additive, the anti-knock additive and the self-repairing additive is 4:1.5:1, and the film-forming additive, the anti-knock additive and the self-repairing additive are fluoroethylene carbonate, triphenylphosphine and polyvinylidene fluoride, respectively; The lithium salt is lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide) and lithium trifluoromethanesulfonate, and the molar ratio of lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide) and lithium trifluoromethanesulfonate is 3:1:2.5; S3, the pore size of the ultrafiltration membrane filter is 38 nm, and the rest is the same as in Example 1; S4. Same as in Embodiment 1.

[0022] Embodiment 3, a method for preparing a high-voltage resistant lithium battery electrolyte, the method for preparing the lithium battery electrolyte comprising: S1, add 90g of the base solvent into a mixing container, stir at 800rpm for 30 minutes, then add 10g of the special functional solvent, and continue stirring for 48 minutes; The base solvent includes propylene carbonate, diethyl carbonate and ethyl methyl carbonate, and the molar ratio of propylene carbonate, diethyl carbonate and ethyl methyl carbonate is 3:1:2; The special functional solvent includes fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate, the addition amount of the special functional solvent is 15% of the total mass of the base solvent, and the molar ratio of fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate is 2:1:3; S2. The additive is made into nano-sized particles by ultrasonic dispersion method, the ultrasonic frequency is 43kHz, the power is 270W, the lithium salt is prepared into nano-sized crystals by solvent thermal method, the solvent thermal reaction temperature is 190°C, the reaction time is 11 hours, and the nano-sized particle additive and the nano-sized crystalline lithium salt are dispersed in a mixed solution of a base solvent and a special functional solvent to obtain a crude electrolyte; The additives include a new film-forming additive, an anti-knock additive and a self-repairing additive, the molar ratio of the film-forming additive, the anti-knock additive and the self-repairing additive is 4:1.5:1, and the film-forming additive, the anti-knock additive and the self-repairing additive are vinylene carbonate, trimethyl phosphate and polyvinylidene fluoride, respectively; The lithium salt is lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide) and lithium trifluoromethanesulfonate, and the molar ratio of lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide) and lithium trifluoromethanesulfonate is 4:1:3; S3, the pore size of the ultrafiltration membrane filter is 48 nm, and the rest is the same as in Example 1; S4. Same as in Embodiment 1.

[0023] Embodiment 4, a method for preparing a high-voltage resistant lithium battery electrolyte, the method for preparing the lithium battery electrolyte comprising: S5. Perform performance testing on the electrolyte after aging treatment.

[0024] The parameters tested include conductivity, oxidation potential, reduction potential, lithium ion transference number, viscosity, density, moisture content, impurity content, fluoride stability, high voltage stability, thermal stability, appearance change, odor change, and microstructural change.

[0025] The performance test results of Examples 1, 2 and 3 are as follows: In Example 1, the conductivity of the electrolyte reaches 10.2mS / cm, the oxidation potential is 4.4VvsLi / Li+, the reduction potential is 1.3VvsLi / Li+, the lithium ion migration number is 0.45, the viscosity measurement result is 2.3mPa·s, the density is 1.24g / cm³, the moisture content is controlled at 18ppm, the impurity content is about 25ppm, the fluoride stability is stable, the high-voltage stability is outstanding, and it can work stably under a high voltage of 4.7V. In terms of thermal stability, it can withstand temperatures as high as 200°C without obvious decomposition. In terms of appearance, the electrolyte always remains clear and transparent, without signs of turbidity and discoloration, no abnormal odor, uniform microstructure, good dispersion of additives and lithium salt particles, and no agglomeration precipitation.

[0026] In Example 2, the conductivity climbed to 11.5mS / cm, the lithium ion migration number increased to 0.48, the battery charge and discharge rate was accelerated, the oxidation potential reached 4.5VvsLi / Li+, the reduction potential dropped to 1.2VvsLi / Li+, the battery charge and discharge window was widened, the viscosity was fine-tuned to 2.1mPa·s, the fluidity was better, the density increased to 1.27g / cm³, the moisture content was as low as 15ppm, the impurity content was 20ppm, the purity was higher, the high-voltage stability could withstand 4.9V, the thermal stability was improved to 210℃ without decomposition, the appearance, odor and microstructure remained in an ideal state without any degradation.

[0027] In Example 3, the conductivity is as high as 12.3mS / cm, the lithium ion migration number is 0.50, the ion conduction efficiency is outstanding, the oxidation potential is 4.6VvsLi / Li+, and the reduction potential is 1.1VvsLi / Li+, which lays a solid foundation for efficient charging and discharging of the battery. The viscosity is reduced to 2.0mPa·s, the density is 1.29g / cm³, the moisture content is only 12ppm, the impurity content is 18ppm, the purity is extremely high, the high-voltage stability can withstand 5.1V, the thermal stability reaches 220℃ without decomposition, the appearance is clear, the odor is normal, the components are evenly dispersed in the microstructure, and the high-performance operation of the battery is maintained for a long time.

[0028] In summary, by performing performance tests on the high-voltage lithium battery electrolytes prepared under different conditions in Examples 1, 2, and 3, with the adjustment of the dosage ratio of the basic solvent and the special functional solvent, and the gradual optimization of process parameters such as ultrasonic dispersion and solvent thermal reaction, the various properties of the electrolytes showed an increasingly better trend.

[0029] From the perspective of conductivity, the value continues to increase, which means that the ion conduction capacity continues to increase, which is more conducive to the rapid transfer of electricity during the battery charging and discharging process, and improves the battery charging and discharging efficiency. The gradual increase in the number of lithium ion migration also confirms this, indicating that the obstacles to the movement of lithium ions in the electrolyte are getting smaller and smaller.

[0030] In terms of potential, the oxidation potential gradually increases and the reduction potential gradually decreases, which broadens the battery's charge and discharge window, allowing the battery to operate stably within a wider voltage range, helping to improve the battery's overall energy utilization efficiency and performance.

[0031] Changes in viscosity and density also tend to be more conducive to the function of the electrolyte. Appropriate viscosity ensures good fluidity, allowing it to fully contact the electrode without hindering the movement of ions, while reasonable changes in density help maintain the stability of the internal structure of the battery.

[0032] The moisture content and impurity content continue to decrease, reflecting that the optimization effect of degassing and filtration and other impurity removal processes in the preparation process is significant. The lower content greatly reduces the adverse phenomena such as short circuit and gas production caused by moisture or impurities inside the battery, thereby improving the safety and stability of the battery.

[0033] Moreover, it has outstanding performance and is gradually improving in terms of fluoride stability, high-voltage stability and thermal stability, which can better adapt to the use requirements of lithium batteries in different working conditions, especially in complex environments such as high energy density, high voltage and high temperature. At the same time, the appearance, odor and microstructure always remain in good condition, further ensuring that the electrolyte can stably help lithium batteries achieve high-performance operation in a long-term manner.

[0034] Examples 1, 2 and 3 demonstrate the feasibility and effectiveness of the method for preparing a high-voltage lithium battery electrolyte and the operability of improving electrolyte performance by adjusting process parameters, providing a valuable reference for further optimization and industrial production of high-performance lithium battery electrolytes. The high-voltage lithium battery electrolyte mentioned in Example 5 is obtained based on the above preparation method.

[0035] Embodiment 5: A high-voltage-resistant lithium battery electrolyte is prepared according to a method for preparing a high-voltage-resistant lithium battery electrolyte.

[0036] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a high-voltage resistant lithium battery electrolyte, characterized in that: The preparation method of lithium battery electrolyte comprises: S1. Add the base solvent into the mixing container and stir with a high-speed magnetic stirrer at a stirring speed of 800 rpm for 30 minutes, then add the special functional solvent and continue stirring for 48 minutes. The mixing mass ratio of the base solvent to the special functional solvent is 7:3-9:

2. S2. The additive is made into nano-sized particles by ultrasonic dispersion method, the lithium salt is prepared into nano-sized crystals by solvothermal method, and the nano-sized particle additive and the nano-sized crystalline lithium salt are dispersed in a mixed solution of a basic solvent and a special functional solvent to obtain a crude electrolyte; S3, degassing the crude electrolyte under a high vacuum environment, with the vacuum degree reaching below 0.005 KPa, and removing impurities and solid particles through an ultrafiltration membrane filter, the pore size of the ultrafiltration membrane filter is 28-48 nm, to obtain a purified electrolyte; S4, placing the electrolyte in a thermostat, connecting the nitrogen supply pipeline and opening the thermostat to perform electrolyte aging treatment; S5. Performing performance testing on the electrolyte after aging treatment; The base solvent includes propylene carbonate, diethyl carbonate and ethyl methyl carbonate, and the molar ratio of propylene carbonate, diethyl carbonate and ethyl methyl carbonate is 3:1:2; The special functional solvents include fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate. The addition amount of the special functional solvent is 10%-15% of the total mass of the base solvent, and the molar ratio of fluoropropylene carbonate, fluorodiethyl carbonate and perfluoroethyl methyl carbonate is 1:1:2-2:1:

3.

2. The method for preparing a high-voltage-resistant lithium battery electrolyte according to claim 1, characterized in that: The additives include a novel film-forming additive, an anti-knock additive and a self-repairing additive, wherein the molar ratio of the film-forming additive, the anti-knock additive and the self-repairing additive is 4:1.5:1; The film-forming additive is one or more of vinylene carbonate or fluoroethylene carbonate, the anti-knock additive is one or more of trimethyl phosphate or triphenylphosphine, and the self-repairing additive is polyvinylidene fluoride.

3. The method for preparing a high-voltage resistant lithium battery electrolyte according to claim 1, characterized in that: The lithium salt is lithium tetrafluoroborate, lithium bistrifluoromethanesulfonyl imide and lithium trifluoromethanesulfonate, and the molar ratio of lithium tetrafluoroborate, lithium bistrifluoromethanesulfonyl imide and lithium trifluoromethanesulfonate is 2:1:2-4:1:

3.

4. The method for preparing a high-voltage-resistant lithium battery electrolyte according to claim 1, characterized in that: The frequency of ultrasonic dispersion is 26-43 kHz, the power is 120-270 W, the solvent thermal reaction temperature is 160-190° C., and the reaction time is 7-11 hours.

5. The method for preparing a high-voltage-resistant lithium battery electrolyte according to claim 1, characterized in that: The temperature of the thermostat was set at 28°C. After the temperature stabilized, nitrogen was introduced at a nitrogen flow rate of 0.6 liters per minute. The aging time was 10 days. During the aging process, samples were taken every 8 hours for performance testing.

6. The method for preparing a high-voltage-resistant lithium battery electrolyte according to claim 1, characterized in that: The parameters tested include conductivity, oxidation potential, reduction potential, lithium ion transference number, viscosity, density, moisture content, impurity content, fluoride stability, high voltage stability, thermal stability, appearance change, odor change, and microstructural change.

7. A high-voltage-resistant lithium battery electrolyte, characterized in that: The electrolyte is prepared according to the method for preparing a high-voltage resistant lithium battery electrolyte according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • A lithium battery electrolyte and a lithium battery

    CN111261924B

  • A lithium battery electrolyte and a lithium battery

    CN113972395B

  • Electrolytes for lithium batteries and lithium batteries

    JP4754323B2

  • Electrolyte fluid metering device for lithium cells

    KR102020194B1

  • High-voltage lithium ion battery and electrolyte thereof

    CN103078138A